Topography of the Aleutian Trench south-east off Bowers Ridge, Bering Sea, in the context of the geological development of North Pacific Ocean - Lemenkova, Polina (2021)
The research is focused on the topographic modelling and mapping of the Aleutian Trench. The study area is situated in the Bering Sea, a marginal sea located northernmost of the Pacific Ocean, between Alaska and Kamchatka Peninsula. The geological setting of the region is characterized by the subduction of the oceanic Pacific Plate below the continental North American Plate. Other features include high seismic activity along the Aleutian island arcs bordering the oceanic seafloor. The objective of this paper is to explore the interaction between the geophysical setting affecting the relief of the seafloor by using geoinformation techniques and geological analysis. In the hypothesis of this study, variations in the geophysical fields as independent variables are reflected in the morphology of the seafloor, which can be observed using data visualization by the advanced cartographic scripting solutions. The open source high-resolution topographic map (ETOPO1), marine free-air gravity and Bouguer gravity anomaly data were used and integrated to investigate the potential correlation between the geophysical, geological, tectonic and topographic settings of the Bering Sea. Our main method includes bathymetric mapping of the area with publicly available bathymetric data using GMT. Materials include open source data: ETOPO1 raster grid with 1 arc-minute resolution, EGM96 gravity and vector contour layers of GMT. The research included complex thematic mapping of the region, including topographic, contour, geodetic and geophysical mapping, 3D modelling and geomorphological plotting of the 30 cross-section segments of the trench located SE off the Bowers Ridge. According to the processed ETOPO1 dataset, the minimal depth is -8480 m and the mean is -3089.154 m. The geoid undulations model shows that the majority of the gravity values lie in the interval between -10 and 20 m with the lowest values along the trench. The statistical histogram shows that the most common depth value in the segment of the Aleutian Trench is -4800 ...